2024
DOI: 10.1038/s41598-024-51811-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between environmental mercury exposure and allergic disorders in Korean children: Korean National Environmental Health Survey (KoNEHS) cycles 3–4 (2015–2020)

Ji-youn Lee,
Yun-Hee Choi,
Hyeon-il Choi
et al.

Abstract: Although previous studies have suggested potential adverse effects of mercury on a child’s immune system, the associations have been inconsistent. We aimed to determine the association between urinary mercury levels and allergic diseases in Korean children with high mercury exposure. Data from 853 and 710 children aged 6–11 years in the Korean National Environmental Health Survey (KoNEHS) cycle 3 (2015–2017) and cycle 4 (2018–2020) were analyzed. We examined the association between mercury exposure and the pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(58 reference statements)
0
1
1
Order By: Relevance
“…A cycle of cross-sectional studies conducted in Korea on children aged 6-11 years found that serum mercury levels had a positive correlation with the risk of atopic dermatitis and a high positive correlation with asthma. The latter result does not coincide with previous studies conducted in Germany and USA, in which no correlation with asthma was found; however, this can be explained by the higher average mercury (Hg) level in Korean children [58]. The average mercury levels in children in the cited study were 0.40 µg/L, higher than those in the US NHANES (2015-2016) (0.25 µg/L for 3-11-year-olds) and Germany GerES V (2014-2017) (0.068 µg/L for 5-9-year-olds) in similar periods and age groups.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…A cycle of cross-sectional studies conducted in Korea on children aged 6-11 years found that serum mercury levels had a positive correlation with the risk of atopic dermatitis and a high positive correlation with asthma. The latter result does not coincide with previous studies conducted in Germany and USA, in which no correlation with asthma was found; however, this can be explained by the higher average mercury (Hg) level in Korean children [58]. The average mercury levels in children in the cited study were 0.40 µg/L, higher than those in the US NHANES (2015-2016) (0.25 µg/L for 3-11-year-olds) and Germany GerES V (2014-2017) (0.068 µg/L for 5-9-year-olds) in similar periods and age groups.…”
Section: Discussioncontrasting
confidence: 91%
“…The average mercury levels in children in the cited study were 0.40 µg/L, higher than those in the US NHANES (2015-2016) (0.25 µg/L for 3-11-year-olds) and Germany GerES V (2014-2017) (0.068 µg/L for 5-9-year-olds) in similar periods and age groups. According to some studies, the higher mercury (Hg) levels in the Korean child population can be attributed partly to dietary habits (consisting of heavy consumption of grains and seafood) and partly to air pollution [58,59]. Regarding potential alterations in cognitive functions, a study based on the systematic review of 1573 articles observed concordant results indicating an association between heavy metal (HM) exposure and decreased neurocognitive function in adults.…”
Section: Discussionmentioning
confidence: 99%